A facile synthesis approach of silica aero-gel/eicosane particles and its potential application on polyester fabric to impart thermoregulation properties - Moni Sankar Mondal; Syed Zubair Hussain; Mohammad Ullah (Heliyon, 2023)
This article aims to study the thermo-regulating properties of infiltrated Phase change material (PCM) micro-particles treated on polyester fabric. The melt infiltration method was implemented for the synthesis of the Silica aero-gel/Eicosane particles by dispersing eicosane in silica aero-gel. Synthesized particles were incorporated into the polyester knitted fabric by both exhaustion dyeing and coating method to impart the thermoregulation characteristics. The crystalline structure and the particle size of aero-gel infiltrated PCM particles were measured by X-ray diffraction (XRD) analyzer. The presence of eicosane particles deposited on the fabric surface was confirmed by the Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscope (SEM). Finally, while the sample was subjected to heating, both the dyed and coated fabric showed resistance against the rise of temperature due to the presence of phase transition PCM micro-particles compared to the untreated raw fabric sample.